A peek into diversity of terrestrial cyanobacteria collected in San Gerardo de Rivas region, Costa Rica. - Hauerová, Radka (Jihočeská univerzita, 2017)
The presented thesis focuses on diversity of cyanobacteria collected from terrestrial habitats in the surroundings of San Gerardo de Rivas, Costa Rica. The first part of this thesis consists of a floristic survey performed on dried and subsequently revived samples using light microscopy. The second part introduces new cyanobacterial genus Calochaete (Microchaetaceae, Nostocales) with the type species C. cimrmanii.
A peek into diversity of terrestrial cyanobacteria collected in San Gerardo de Rivas region, Costa Rica.
Keywords: cyanobacteria; Costa Rica; biodiversity; floristic survey; cyanobacteria; Costa Rica; biodiversity; floristic survey